Identification of novel genetic and epigenetic regulators of different tissue types of cervical cancer. Issue 12 (2nd October 2022) - Chandra, Sanchita; Sarkar, Subham; Mandal, Paramita
Abstract: Objectives: The study aimed to find differential gene mutations, DNA methylation, and expression profiles among different categories of cervical cancer samples. Methods: The study was based on freely available gene mutations, promoter methylation, and gene expression status of The Cancer Genome Atlas (TCGA) cervical cancer samples and adjacent normal tissues in the Genomic Data Commons (GDC) portal. The association of CpG island methylation with gene expression was determined through negative correlation analysis. Results: We identified that the ErbB signaling pathway and proteoglycans pathway was significantly associated with adenocarcinoma cervical cancers patients. In these pathways, missense mutation especially S310F in the ERBB2 gene as well as G12D and A146T in the KRAS gene were significantly associated with adenocarcinoma cases. Furthermore, a comparison of SCC cases with adjacent control tissues revealed differential hypermethylation of two CpG positions of the KAAG1 gene and differential downregulation of NPY1R and NPY5R genes in cervical squamous cell carcinoma compared to cervical adenocarcinoma cases and adjacent normal tissues. Specifically, the hypermethylation of the promoter region of the KAAG1 gene might be responsible for the carcinogenesis of cervical squamous cells exclusively and methylation marks can be reversible by the widely used drug, azacytidine. In contrast, adenocarcinoma cervical cancer cases may be treated with floxuridine which is successfully utilized for other tissue‐specific adenocarcinoma cases. Conclusions: These results provide valuable insight into the differential molecular markers among the categories of cervical cancer, which helps our ability to classify these cancers and for targeted therapy.